Aluminum nitride / cobalt-based MOF porous carbon composite material wave-absorbing agent as well as preparation method and application thereof
By pyrolyzing the cobalt-based MOF and solvothermal reaction with aluminum nitride and N,N-dimethylformamide, an aluminum nitride/cobalt-based MOF porous carbon composite absorber was prepared, which solved the problem of small reflection loss of existing MOF derivatives and achieved efficient electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202510088080.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
The existing MOF derivatives have a problem of small reflection loss in the field of electromagnetic wave absorption, which limits their practical application.
By pyrolyzing the cobalt-based MOF, a cobalt-based MOF porous carbon was obtained, and solvothermal reaction was carried out with aluminum nitride and N,N-dimethylformamide to prepare an aluminum nitride/cobalt-based MOF porous carbon composite absorber.
The reflection loss of the aluminium nitride/cobalt-based MOF porous carbon composite absorber is significantly improved, with the maximum reflection loss reaching -43.20dB, improving its absorption performance and practical application feasibility in multiple bands.
Smart Images

Figure CN119873792A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to an aluminum nitride / cobalt-based MOF porous carbon composite wave absorbing agent, and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic communication equipment, electromagnetic pollution has become increasingly prominent, and electromagnetic absorbing materials have received extensive attention. Metal organic framework (MOF) derived materials are a new type of absorbing material with advantages such as simple synthesis process, low production cost, and good thermal stability. The derived porous carbon / magnetic metal particle composite material overcomes the problem of uneven dispersion of magnetic particles, so it has attracted widespread attention in the field of absorbing.
[0003] MOF derivatives, especially carbon-based absorbing materials derived from ZIF-67 as a precursor, are the focus of current research, which is of great significance to the research on microwave absorbing materials derived from heterogeneous metal MOFs and their performance applications. However, the problem of low reflection loss in single-component MOFs greatly limits the practical application of this type of absorbing materials. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an aluminum nitride / cobalt-based MOF porous carbon composite absorber and a preparation method and application thereof. The aluminum nitride / cobalt-based MOF porous carbon composite absorber prepared by the present invention has high reflection loss.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing an aluminum nitride / cobalt-based MOF porous carbon composite material absorber, comprising the following steps:
[0007] The cobalt-based MOF is pyrolyzed and carbonized to obtain cobalt-based MOF porous carbon;
[0008] The cobalt-based MOF porous carbon, aluminum nitride (AlN) and N,N-dimethylformamide are mixed to undergo a solvent thermal reaction to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
[0009] Preferably, the cobalt-based MOF comprises ZIF-67.
[0010] Preferably, the pyrolysis carbonization comprises the following steps: heating to 400-900°C at a rate of 5°C / min, keeping the temperature for 2 hours, and then cooling to room temperature at a rate of 5°C / min.
[0011] Preferably, the mass ratio of the aluminum nitride to the cobalt-based MOF porous carbon is 3-9:1-7.
[0012] Preferably, the mass ratio of the aluminum nitride to the cobalt-based MOF porous carbon is 3:7, 7:3, 8:2 or 9:1.
[0013] Preferably, the usage ratio of aluminum nitride to N,N-dimethylformamide is 5g:200mL.
[0014] Preferably, the temperature of the solvent thermal reaction is 120-160° C., and the time is 12-24 hours.
[0015] Preferably, after the solvothermal reaction is completed, the obtained mixed solution is sequentially washed, solid-liquid separated and dried to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
[0016] The present invention also provides an aluminum nitride / cobalt-based MOF porous carbon composite material absorber prepared by the preparation method described in the above technical solution.
[0017] The present invention also provides the use of the aluminum nitride / cobalt-based MOF porous carbon composite material absorber described in the above technical solution as an electromagnetic wave absorber in military stealth, electronic information and biomedical imaging.
[0018] The invention provides a method for preparing an aluminum nitride / cobalt-based MOF porous carbon composite material wave absorber, comprising the following steps: pyrolyzing and carbonizing cobalt-based MOF to obtain cobalt-based MOF porous carbon; and mixing the cobalt-based MOF porous carbon, aluminum nitride and N,N-dimethylformamide to perform a solvent thermal reaction to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material wave absorber.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention uses cobalt-based MOF as a carbon source precursor, and uses cobalt-based MOF porous carbon obtained by pyrolyzing and carbonizing cobalt-based MOF as a basic carbon source material, combined with AlN, to significantly improve the wave absorption performance of cobalt-based MOF, and improve the reflection loss of aluminum nitride / cobalt-based MOF porous carbon composite absorber. The data of the embodiment show that the maximum reflection loss of the aluminum nitride / cobalt-based MOF porous carbon composite absorber prepared by the present invention is -43.20dB. The preparation method of the present invention has low cost, high yield, and is easy to prepare.
[0021] Furthermore, the present invention limits the mass ratio of aluminum nitride and cobalt-based MOF porous carbon, regulates the charge distribution and proportion of dielectric / magnetic materials to achieve optimal impedance matching, can effectively improve the ability of reflection loss and improve the effective absorption bandwidth, and realize flexible regulation of electromagnetic waves in multiple bands. While ensuring the light weight of the material itself, the thickness of the coating is also relatively thin, which is conducive to making more meaningful research on the realization of the ultimate goal of "thin, light, wide and strong" of the absorbing material. While ensuring the ultra-thin thickness (1 to 6 mm), the absorbing performance of the cobalt-based MOF is improved, and ultimately the practical application feasibility and commercial utilization value of MOF-based binary carbon nano-absorbing materials are improved.
[0022] The present invention also provides an aluminum nitride / cobalt-based MOF porous carbon composite material absorber prepared by the preparation method described in the above technical scheme, which is a binary composite nano-absorbent material that can break through the problem that MOF single material is limited in the field of electromagnetic wave absorption. This material is applied to the field of electromagnetic wave absorption (including military stealth, electronic information and biomedical imaging), and has good development potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of the aluminum nitride / cobalt-based MOF porous carbon composite absorber prepared in Example 1 at a low magnification;
[0024] Figure 2 This is a SEM image of the aluminum nitride / cobalt-based MOF porous carbon composite absorber prepared in Example 1 at high magnification. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing an aluminum nitride / cobalt-based MOF porous carbon composite material absorber, comprising the following steps:
[0026] The cobalt-based MOF is pyrolyzed and carbonized to obtain cobalt-based MOF porous carbon;
[0027] The cobalt-based MOF porous carbon, aluminum nitride and N,N-dimethylformamide are mixed to undergo a solvent thermal reaction to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
[0028] The present invention performs pyrolysis and carbonization on the cobalt-based MOF to obtain the cobalt-based MOF porous carbon.
[0029] In the present invention, the cobalt-based MOF preferably includes ZIF-67, and the ZIF-67 has a unique rhombic dodecahedron structure after pyrolysis and carbonization, and the skeleton is stable.
[0030] The present invention has no particular limitation on the specific source of the ZIF-67, and it can be prepared by a source or a conventional preparation method known to those skilled in the art. In a specific embodiment of the present invention, the preparation method of the ZIF-67 comprises the following steps:
[0031] Prepare cobalt nitrate hexahydrate and dimethylimidazole respectively, measure methanol and pour it into beaker respectively, dissolve cobalt nitrate hexahydrate and dimethylimidazole into methanol respectively, place on magnetic stirrer and stir at room temperature for 1 hour, after stirring for 1 hour, add the methanol solution containing cobalt nitrate hexahydrate into the methanol solution containing dimethylimidazole and stir at room temperature for 24 hours, centrifuge the stirred solution in a centrifuge, and then wash, put the washed solution into a vacuum oven with the temperature set to 60°C and the drying time 8 hours, and turn off the instrument after the drying to obtain the ZIF-67.
[0032] In the present invention, the pyrolysis carbonization preferably includes the following steps: heating to 400-900°C (specifically 400, 500, 600, 700, 800 or 900°C) at a rate of 5°C / min, keeping warm for 2 hours, and then cooling to room temperature at a rate of 5°C / min. Under the conditions of this pyrolysis carbonization, the cobalt-based MOF can be converted into cobalt-based MOF porous carbon.
[0033] In the present invention, the pyrolysis carbonization is preferably carried out in a tube furnace.
[0034] In the present invention, the particle size of the cobalt-based MOF porous carbon is preferably 500-900 nm, specifically 500, 600, 700, 800 or 900 nm.
[0035] After obtaining the cobalt-based MOF porous carbon, the present invention mixes the cobalt-based MOF porous carbon, aluminum nitride and N,N-dimethylformamide to perform a solvent thermal reaction to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
[0036] In the present invention, the mass ratio of the aluminum nitride and the cobalt-based MOF porous carbon is preferably 3 to 9:1 to 7, specifically 3:7, 7:3, 8:2 or 9:1. The mass ratio of the aluminum nitride to the cobalt-based MOF porous carbon has a great influence on the wave absorbing properties of the composite material. However, as the ratio of the two continues to increase, the aluminum nitride cannot fully modify the cobalt-based MOF porous carbon, and more aluminum nitride agglomeration phenomenon intensifies, and the dispersion decreases, which hinders the conductive circuit formed between the aluminum nitride and the cobalt-based MOF porous carbon layer, thereby inhibiting the wave absorbing properties of the entire composite material.
[0037] In the present invention, the aluminum nitride is preferably irregular particles, and the average diameter is preferably 40 to 100 nm, specifically 40, 50, 60, 70, 80, 90 or 100 nm. The role of the aluminum nitride is to regulate the dielectric, polarization and impedance matching of the aluminum nitride / cobalt-based MOF porous carbon composite absorber, and the average diameter of the aluminum nitride is controlled within the above range. The aluminum nitride has a high specific surface area and a low volume density, and can be better composited on the cobalt-based MOF porous carbon.
[0038] In the present invention, the usage ratio of aluminum nitride to N,N-dimethylformamide is preferably 5g:200mL.
[0039] In the present invention, the N,N-dimethylformamide is preferably added into a reaction container, and then the aluminum nitride and the cobalt-based MOF porous carbon are added in sequence and mixed, and then the solvent thermal reaction is carried out.
[0040] In the present invention, the temperature of the solvothermal reaction is preferably 120-160° C., specifically 120, 140 or 160° C., and the time is preferably 12-24 h, specifically 12, 16, 20 or 24 h.
[0041] In the present invention, during the solvothermal reaction, the aluminum nitride is composited onto the skeleton of the cobalt-based MOF porous carbon.
[0042] In the present invention, the temperature of the solvothermal reaction is preferably provided by an oil bath.
[0043] In the present invention, after the solvothermal reaction is completed, the obtained mixed solution is preferably washed, solid-liquid separated and dried in sequence to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
[0044] In the present invention, the washing detergent preferably includes anhydrous ethanol; the solid-liquid separation is preferably centrifugal; the drying is preferably carried out in a drying oven, the drying temperature is preferably 60° C., and the drying time is preferably 12 hours.
[0045] The present invention also provides an aluminum nitride / cobalt-based MOF porous carbon composite material absorber prepared by the preparation method described in the above technical solution.
[0046] In the present invention, the dielectric constant of the aluminum nitride / cobalt-based MOF porous carbon composite absorber preferably includes: real part: 1.21 to 1.00, imaginary part: 0.19 to 0.00; the magnetic permeability preferably includes: real part: 26.86 to 5.39, imaginary part: 31.24 to 0.26; the reflection loss is preferably -10.10 to -43.20 dB; and the absorption bandwidth is preferably 2 to 18 GHz.
[0047] The present invention preferably uses a vector network analyzer coaxial method to test the electromagnetic parameters of the aluminum nitride / cobalt-based MOF porous carbon composite material absorber. During the test, the thickness of the sample to be tested is preferably 1 to 6 mm, specifically 1, 2, 3, 4, 5 or 6 mm.
[0048] The present invention also provides the use of the aluminum nitride / cobalt-based MOF porous carbon composite material absorber described in the above technical solution as an electromagnetic wave absorber in military stealth, electronic information and biomedical imaging.
[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Sources of raw materials for the embodiments of the present invention and the comparative examples: cobalt nitrate hexahydrate from Shanghai Aladdin Biochemical Technology Co., Ltd., with a content of ≥99.0wt%; dimethylimidazole from Shanghai Aladdin Biochemical Technology Co., Ltd., with a content of ≥98.0wt%; anhydrous ethanol from Tianjin Lishi Comeo Chemical Reagent Co., Ltd., with a content of ≥99.7wt%; methanol from Tianjin Lishi Comeo Chemical Reagent Co., Ltd., with a content of ≥99.9wt%; aluminum nitride from Beijing Dekedao Jinji Technology Co., Ltd., with an average particle size of 40 to 100nm; N,N-dimethylformamide from Tianjin Lishi Comeo Chemical Reagent Co., Ltd., with a content of ≥99.5wt%.
[0051] The electromagnetic parameters (dielectric constant and magnetic permeability) of the sample are tested by the coaxial method of a vector network analyzer, including the following steps:
[0052] The prepared sample was mixed with solid paraffin, and then evenly poured into a special pressing ring mold (the coaxial method test requires a fixed-size annular paraffin ring) to press the mixed powder into a ring to obtain an annular sample with an inner diameter of 3.04mm and an outer diameter of 7.00mm, and corresponding markings were made; the vector network analyzer was produced by Agilent (KEYSIGHT), model N5232B; the reflection loss calculation formula was used to obtain the absorbing performance of the corresponding material.
[0053] Calculate the reflection loss variation of the sample at frequencies from 2 to 18 GHz.
[0054] Example 1
[0055] Weigh cobalt nitrate hexahydrate and dimethylimidazole in a molar ratio of 1:4, and then measure methanol and pour it into two beakers. Add the weighed cobalt nitrate hexahydrate and dimethylimidazole into methanol and add a magnet. Seal the beakers with plastic wrap to prevent the volatilization of the two solutions. After sticking the plastic wrap, place them all on a magnetic stirrer and stir at room temperature for 1 hour. After stirring for 1 hour, add the methanol solution containing cobalt nitrate hexahydrate to the methanol solution containing dimethylimidazole and stir at room temperature for 24 hours. Centrifuge and wash the stirred solution in a centrifuge. Put the washed solution into a vacuum oven and dry it at 60°C for 8 hours to obtain ZIF-67, which is then marked and stored.
[0056] ZIF-67 was placed in a tubular furnace for pyrolysis and carbonization. The temperature was raised at a rate of 5°C / min for 140 minutes to 700°C. After reaching 700°C, it was kept warm for 2 hours, and then cooled at a rate of 5°C / min for 140 minutes to room temperature. After the cooling was completed, the instrument was turned off to obtain cobalt-based MOF porous carbon with a particle size of 600nm. The reflection loss of the obtained cobalt-based MOF porous carbon was -9.04dB.
[0057] Weigh 0.3g AlN and 0.7g cobalt-based MOF porous carbon particles and dissolve them in N,N-dimethylformamide (the ratio of aluminum nitride to N,N-dimethylformamide is 5g:200mL). The stirring time is 24h and the stirring temperature is 120℃ for solvent thermal reaction. After the reaction is completed, turn off the instrument and let the whole device cool naturally to room temperature. Then wash the obtained mixed solution with anhydrous ethanol and centrifuge it, and then place it in a drying oven for drying. The temperature is set to 60℃ and the drying time is 12h to obtain an aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
[0058] Figure 1 This is a SEM image of the aluminum nitride / cobalt-based MOF porous carbon composite material absorber prepared in Example 1 at a low magnification. Figure 2 This is a SEM image of the aluminum nitride / cobalt-based MOF porous carbon composite material absorber prepared in Example 1 at a high magnification. It can be seen that the aluminum nitride / cobalt-based MOF porous carbon composite material absorber was successfully prepared.
[0059] After the aluminum nitride / cobalt-based MOF porous carbon composite absorber obtained in this embodiment was mixed with paraffin (the mass ratio of the aluminum nitride / cobalt-based MOF porous carbon composite absorber to paraffin was 4:6), the absorbing performance was tested under the conditions of a test frequency of 2 to 18 GHz and a sample thickness of 1.1 mm: the real part of the dielectric constant: 1.21 to 1.01, the imaginary part of the dielectric constant: 0.19 to 0.01; the real part of the magnetic permeability: 26.86 to 14.2, the imaginary part of the magnetic permeability: 31.24 to 9.13, and the reflection loss was -10.10 dB.
[0060] Example 2
[0061] The same as Example 1, the only difference is that: ZIF-67 is placed in a tubular furnace for pyrolysis and carbonization, the temperature is increased to 400°C at a rate of 5°C / min, and after reaching 400°C, it is kept warm for 2h, and then cooled to room temperature at a rate of 5°C / min. After the cooling is completed, the instrument is turned off to obtain cobalt-based MOF porous carbon with a particle size of 600nm, and the reflection loss of the obtained cobalt-based MOF porous carbon is -0.86dB.
[0062] Example 3
[0063] The same as Example 1, the only difference is: ZIF-67 is placed in a tubular furnace for pyrolysis and carbonization, the temperature is increased to 500°C at a rate of 5°C / min, and then kept warm for 2 hours after reaching 500°C, and then cooled to room temperature at a rate of 5°C / min. After the cooling is completed, the instrument is turned off to obtain cobalt-based MOF porous carbon with a particle size of 600nm, and the reflection loss of the obtained cobalt-based MOF porous carbon is -0.84dB.
[0064] Example 4
[0065] The same as Example 1, the only difference is: ZIF-67 is placed in a tubular furnace for pyrolysis and carbonization, the temperature is increased to 600°C at a rate of 5°C / min, and after reaching 600°C, it is kept warm for 2h, and then cooled to room temperature at a rate of 5°C / min. After the cooling is completed, the instrument is turned off to obtain cobalt-based MOF porous carbon with a particle size of 600nm, and the reflection loss of the obtained cobalt-based MOF porous carbon is -8.28dB.
[0066] Example 5
[0067] The same as Example 1, the only difference is that: ZIF-67 is placed in a tubular furnace for pyrolysis and carbonization, the temperature is increased to 800°C at a rate of 5°C / min, and then kept warm for 2 hours after reaching 800°C, and then cooled to room temperature at a rate of 5°C / min. After the cooling is completed, the instrument is turned off to obtain cobalt-based MOF porous carbon with a particle size of 600nm, and the reflection loss of the obtained cobalt-based MOF porous carbon is -6.94dB.
[0068] Example 6
[0069] The same as Example 1, the only difference is: ZIF-67 is placed in a tubular furnace for pyrolysis and carbonization, the temperature is raised to 900°C at a rate of 5°C / min, and then kept warm for 2 hours after reaching 900°C, and then cooled to room temperature at a rate of 5°C / min. After the cooling is completed, the instrument is turned off to obtain cobalt-based MOF porous carbon with a particle size of 600nm, and the reflection loss of the obtained cobalt-based MOF porous carbon is -5.40dB.
[0070] By comparing Examples 1 to 6, it can be seen that the cobalt-based MOF porous carbon obtained by pyrolysis and carbonization at 700° C. has the largest reflection loss and the best wave absorbing performance.
[0071] Example 7
[0072] The same as Example 1, the only difference is that 0.7 g AlN and 0.3 g cobalt-based MOF porous carbon particles are weighed and dissolved in N,N-dimethylformamide.
[0073] After the aluminum nitride / cobalt-based MOF porous carbon composite absorber obtained in this embodiment was mixed with paraffin (the mass ratio of the aluminum nitride / cobalt-based MOF porous carbon composite absorber to paraffin was 4:6), the absorbing performance was tested under the conditions of a test frequency of 2 to 18 GHz and a thickness of the sample to be tested of 6 mm: the real part of the dielectric constant: 1.13 to 1.00, the imaginary part of the dielectric constant: 0.09 to 0.00; the real part of the magnetic permeability: 11.89 to 9.14, the imaginary part of the magnetic permeability: 4.36 to 2.17, and the reflection loss was -27.10 dB.
[0074] Example 8
[0075] The same as Example 1, the only difference is that 0.8 g AlN and 0.2 g cobalt-based MOF porous carbon particles are weighed and dissolved in N,N-dimethylformamide.
[0076] After the aluminum nitride / cobalt-based MOF porous carbon composite absorber obtained in this embodiment was mixed with paraffin (the mass ratio of the aluminum nitride / cobalt-based MOF porous carbon composite absorber to paraffin was 4:6), the absorbing performance was tested under the conditions of a test frequency of 2 to 18 GHz and a thickness of the sample to be tested of 5.7 mm: the real part of the dielectric constant: 1.08 to 1.00, the imaginary part of the dielectric constant: 0.07 to 0.01; the real part of the magnetic permeability: 8.15 to 6.99, the imaginary part of the magnetic permeability: 1.57 to 0.78, and the reflection loss was -43.20 dB.
[0077] Example 9
[0078] The same as Example 1, the only difference is that 0.9 g AlN and 0.1 g cobalt-based MOF porous carbon particles are weighed and dissolved in N,N-dimethylformamide.
[0079] After the aluminum nitride / cobalt-based MOF porous carbon composite absorber obtained in this embodiment was mixed with paraffin (the mass ratio of the aluminum nitride / cobalt-based MOF porous carbon composite absorber to paraffin was 4:6), the absorbing performance was tested under the conditions of a test frequency of 2 to 18 GHz and a thickness of the sample to be tested of 5.3 mm: the real part of the dielectric constant: 1.07 to 1.01, the imaginary part of the dielectric constant: 0.06 to 0.01; the real part of the magnetic permeability: 6.01 to 5.39, the imaginary part of the magnetic permeability: 0.51 to 0.26, and the reflection loss was -10.62 dB.
[0080] Comparative Example 1
[0081] Cobalt-based MOF porous carbon was prepared according to the method of Example 1.
[0082] After the cobalt-based MOF porous carbon obtained in this comparative example was mixed with paraffin (the mass ratio of cobalt-based MOF porous carbon to paraffin was 4:6), the wave absorption performance was tested under the conditions of a test frequency of 2 to 18 GHz and a thickness of the sample of 3.5 mm: the real part of the dielectric constant: 1.16 to 1.00, the imaginary part of the dielectric constant: 0.16 to 0.01; the real part of the magnetic permeability: 25.94 to 10.88, the imaginary part of the magnetic permeability: 17.84 to 10.13, and the reflection loss was -8.27 dB.
[0083] Comparative Example 2
[0084] Aluminum Nitride.
[0085] After the aluminum nitride and paraffin in this comparative proportion were mixed (the mass ratio of aluminum nitride to paraffin was 4:6), the absorbing performance was tested under the conditions of a test frequency of 2 to 18 GHz and a thickness of the sample of 4.7 mm: the real part of the dielectric constant: 1.03 to 1.01, the imaginary part of the dielectric constant: 0.03 to 0.00; the real part of the magnetic permeability: 4.13 to 3.97, the imaginary part of the magnetic permeability: 0.26 to 0.04, and the reflection loss was -7.47 dB.
[0086] Comparing the embodiments, it can be seen that the reflection loss of Embodiment 8 reaches the maximum, which is -43.20 dB.
[0087] By comparing the embodiments and comparative examples, it can be seen that when the mass ratio of aluminum nitride to cobalt-based MOF porous carbon is 8:2, the wave absorbing performance of the aluminum nitride / cobalt-based MOF porous carbon composite absorber is more excellent, indicating that the addition of aluminum nitride and cobalt-based MOF porous carbon in appropriate proportions greatly improves the wave absorbing performance of the composite material, but as the ratio of the two continues to increase, aluminum nitride cannot fully modify the cobalt-based MOF porous carbon, and more aluminum nitride agglomeration phenomenon intensifies, and the dispersibility decreases, which hinders the conductive loop formed between the aluminum nitride and the cobalt-based MOF porous carbon layer, thereby inhibiting the wave absorbing performance of the entire composite material; and the wave absorbing performance of the cobalt-based MOF porous carbon without adding aluminum nitride is not outstanding, indicating that the aluminum nitride / cobalt-based MOF porous carbon composite absorber of the present invention has great research value; the rationality and feasibility of the addition ratios of aluminum nitride and cobalt-based MOF porous carbon in the embodiment are also verified by the comparative example.
[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing an aluminum nitride / cobalt-based MOF porous carbon composite material absorber, characterized in that: The following steps are involved: The cobalt-based MOF is pyrolyzed and carbonized to obtain cobalt-based MOF porous carbon; The cobalt-based MOF porous carbon, aluminum nitride and N,N-dimethylformamide are mixed to undergo a solvent thermal reaction to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
2. The preparation method according to claim 1, characterized in that: The cobalt-based MOF includes ZIF-67.
3. The preparation method according to claim 1, characterized in that: The pyrolysis carbonization comprises the following steps: heating to 400-900° C. at a speed of 5° C. / min, keeping the temperature for 2 hours, and cooling to room temperature at a speed of 5° C. / min.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the aluminum nitride to the cobalt-based MOF porous carbon is 3-9:1-7.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the aluminum nitride to the cobalt-based MOF porous carbon is 3:7, 7:3, 8:2 or 9:
1.
6. The preparation method according to claim 1 or 4, characterized in that: The usage ratio of the aluminum nitride and N,N-dimethylformamide is 5g:200mL.
7. The preparation method according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 120-160° C. and the time is 12-24 hours.
8. The preparation method according to claim 1, characterized in that: After the solvothermal reaction is completed, the obtained mixed solution is sequentially washed, solid-liquid separated and dried to obtain the aluminum nitride / cobalt-based MOF porous carbon composite material absorber.
9. Aluminum nitride / cobalt-based MOF porous carbon composite material absorber prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the aluminum nitride / cobalt-based MOF porous carbon composite material absorber according to claim 9 as an electromagnetic wave absorber in military stealth, electronic information and biomedical imaging.